Kinetic Modelling of Esterification and Transesterification Processes for Biodiesel Production Utilising Waste-Based Resource - Hazrat M.A.; Rasul M.G.; Khan M.M.K.; Ashwath N.; Silitonga A.S.; Fattah I.M.R.; Mahlia T.M.I. (MDPI, 2023)
Process optimisation and reaction kinetic model development were carried out for two-stage esterification-transesterification reactions of waste cooking oil (WCO) biodiesel. This study focused on these traditional processes due to their techno-economic feasibility, which is an important factor before deciding on a type of feedstock for industrialisation. Four-factor and two-level face-centred central composite design (CCD) models were used to optimise the process. The kinetic parameters for the esterification and transesterification processes were determined by considering both pseudo-homogeneous irreversible and pseudo-homogeneous first-order irreversible processes. For the esterification process, the optimal conditions were found to be an 8.12:1 methanol to oil molar ratio, 1.9 wt.% of WCO for H2SO4, and 60 C reaction temperature for a period of 90 min. The optimal process conditions for the transesterification process were a 6.1:1 methanol to esterified oil molar ratio, 1.2 wt.% of esterified oil of KOH, reaction temperature of 60 C, and a reaction time of 110 min in a batch reactor system; the optimal yield was 99.77%. The overall process conversion efficiency was found to be 97.44%. Further research into reaction kinetics will aid in determining the precise reaction process kinetic analysis in future. 2022 by the authors.